Skill Development: Government Officials’ Efforts to Face Bureaucratic Reform in the Digital Economy Era - Suyasa, P. Tommy Y. Sumatera; Tumanggor, Raja Oloan; Nurbani, Anna (Faculty of Psychology, Universitas Gadjah Mada, 2025)
To improve performance, the government has made various efforts for a bureaucratic reform. As a result, the state civil apparatus (ASN) or civil servants experience various changes in duties. In changing tasks, there are positive/negative perceptions regarding the new way of completing tasks. This research aimed to find out how ASNs anticipate various changes in these tasks. Changes in tasks can cause job insecurity, which is accompanied by a decrease in job satisfaction. Job insecurity is related to worries about losing valuable aspects work. Meanwhile, job satisfaction is an employee's assessment of various aspects of work. The impact of task changes on job insecurity and job satisfaction is facilitated by skills development. Skills development by ASN includes anticipation by increasing knowledge and abilities. Participants in this research were 258 government agency employees in Jakarta. Based on the test results, it was found that task changes can either increase or decrease job satisfaction. When task changes increase the individual's efforts to develop skills; job satisfaction will ultimately increase. On the other hand, if task changes trigger qualitative job insecurity, then job satisfaction will decrease; especially for individuals with prevention focus.